Ethanolic Extracts Of A. Paniculata (burm. f.) Nees And Its Active Compound, Andrographolide, Decrease The Expression Of Glucose Transporters (glut 4) In High Fuctose-Fat Fed Rats - Agung Endro Nugroho,; Mohamad Andrie,; Rina Susilowati,; Arief Nurrochmad,; Endang Lukitaningsih,; Suwijiyo Pramono, (International Journal of Phytomedicine, 2011)
Andrographolide is a major compound (> 4%) of Andrographis paniculata (Burm. f.) Nees. The compound is most active than the other compounds contained in the plant. Previously, the compound was reported showing hypoglycemic activity in type 1 diabetes mellitus (DM) rats. The compound also improved the uptake of glucose in isolated soleus muscle of type 1 DM rats by increasing the GLUT4 expression. The disruption of GLUT4 translocation is a major factor of insulin resistance. In the study, we investigated the effect of andrografolid and ethanolic extract of A. paniculata (Burm. f.) Nees on the GLUT4 expression in high fuctose-fat fed rats, a model of insulin resistant rats. Insulin resistance in rats was induced by high fructose-fat containing 36% fructose, 15% lard and 5% egg yolks in 0.36 g/200g BW for 55 days. In the study, andrographolide and ethanolic extract of A. paniculata (Burm. f.) showed potent hypoglycaemic effects in insulin resistant rats. In addition, these treatments and metformin could restore the depleted GLUT-4 expression in insulin resistant rats. In conclusion, andrographolide and ethanolic extract of A. paniculata (Burm. f.) decreased the blood glucose levels by increasing the GLUT-4 expression in insulin resistant rats.